2015
DOI: 10.4314/ahs.v14i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors affecting knowledge level of Tuberculosis patients in Rajshahi City, Bangladesh

Abstract: Background: The Tuberculosis (TB) control program in Bangladesh is still unsatisfactory due to insufficient knowledge and stigma about TB. Patients with low knowledge may be at higher risk of experiencing delays in diagnosis and appropriate treatment. Objectives: The aims of this study were to identify the knowledge levels of TB and investigate the factors associated with knowledge level among the TB patients in Bangladesh. Methods: A cross-sectional study was conducted at Rajshahi City, Bangladesh. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
6
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 15 publications
(20 reference statements)
8
40
6
5
Order By: Relevance
“…Destruction of vertebral bodes compromises the nutrition of the intervertebral disc and leads to progressive disc destruction and vertebral collapse 10 . In Bangladesh spinal tuberculosis is predominantly a disease of the young and the usual age of presentation is the first three decades of life 11 which is consistent with the present study result. Reports from developed countries indicate a much older patient population and the median age at diagnosis being sixty-one years.…”
Section: Discussionsupporting
confidence: 82%
“…Destruction of vertebral bodes compromises the nutrition of the intervertebral disc and leads to progressive disc destruction and vertebral collapse 10 . In Bangladesh spinal tuberculosis is predominantly a disease of the young and the usual age of presentation is the first three decades of life 11 which is consistent with the present study result. Reports from developed countries indicate a much older patient population and the median age at diagnosis being sixty-one years.…”
Section: Discussionsupporting
confidence: 82%
“…According to the present study, the chance of conversion increased significantly after more than 15 years of occupational experience. According to this study, as education level increased, the prevalence of this disease decreased, which reflects the effect of education level on the observance of the principles of infection control and disease prevention 17,18 . Moreover, in studying the positive TST cases, no active tuberculosis case was reported.…”
Section: Discussionmentioning
confidence: 67%
“…All participants belong to same age range, although, socio-cultural background and religion were different which considered important predictor of knowledge and practice. [21][22][23][24] This study revealed that ethnicity, education and religion didn't influence on knowledge level. Also, study showed change in practice after the education intervention can be sustained for a longer time.…”
Section: Response Of the Participantsmentioning
confidence: 71%